GENERALIZED CHARACTERISTICS OF THE COMPLEX TECHNOLOGICAL SYSTEM OF AIR NAVIGATION SERVICE OF AIR MOVEMENT - Харченко, В. П.; Мелкумян, В. Г. (Proceedings of National Aviation University (archive), 2021)
A generalized model of a complex technological system of air navigation services is considered, which can serve as a basis for studying the structure and characteristics of its elements and algorithms of their interaction in the process of forming and providing "source products" of the system.